A Implikasi Hukum Perjanjian Internasional terhadap Implementasi Otonomi Daerah: Studi tentang Kompetensi Pemerintah Daerah - Ibnu Mardiyanto (Uti Possidetis: Journal of International Law, 2023)
The era of globalization has had a significant impact on the development of communication and information technology, requiring the ability and capacity for international cooperation among all parties, including central and local governments. The reform process in Indonesia has provided autonomy and authority to local governments to engage in international cooperation through international agreements as one way to improve and advance the conditions of the regions. This research uses normative legal research, which focuses on the analysis of legal principles and rules that govern cooperation through international agreements. This study aims to explain the authority of local governments in the formation of international agreements by considering the implementation of regional autonomy. From this research, it can be concluded that international cooperation by local governments as the initiators of international agreements has significant legal implications for the implementation of regional autonomy, especially in terms of utilizing regional potential, improving bilateral relations, developing human resources, and increasing regional competitiveness Keywords: international agreements; regional autonomy; local government authority